Transformational Leadership in The Implementation of Sekolah Penggerak’s Program - Hariyati, Nunuk; Sholeh, Muhamad; Islamiah, Nia (Jurnal Pedagogi dan Pembelajaran, 2023)
Paradigm changes in implementing the independent curriculum are a tough challenge for teachers. Leadership that can facilitate teachers' needs for curriculum changes needs to be considered by all school principals who join the Driving School Program. This research aims to analyze the role of transformational leadership in school principals in supporting the implementation of the independent curriculum. This research uses a qualitative approach with a multi-case study design between school units. The research subjects were taken using a purposive sampling technique, including school principals, foundation administrators, and teachers, who were explored through interviews, observation, and document analysis. The research data were analyzed using constant comparative techniques. The research results show that female school principals have the same vision and mission in improving school quality, namely by supporting policies implemented by the government, namely the driving school program. Leadership that is integrated reflects transformational leadership with four dimensions, which include (1) ideal influence, providing exemplary examples to all members, (2) intellectual stimulation, facilitating both physical facilities and competence, (3) inspirational motivation, providing space and opportunities to communicating and providing motivation in work, as well as (4) individual consideration, paying attention to the competency development needs of its members. Implementing these four dimensions supports the realization of work motivation and commitment, which has implications for achieving teacher welfare and a positive school culture.